PENGARUH PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN, PERTUMBUHAN ASET, DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR DI BEI TAHUN 2014-2016 - Aini, Nur; Anni Syafa’ati, 13.05.52.0050 (Students' Journal of Accounting and Banking, 2018)
The study examines the effect of profitability, liqiudity, farm size, growth of assets, and business risk. This reearch on manufacturing company on the indonesian Stock Exchange by using a go public.The sampling metods used purposive sampling with periode from 2014 to 2016. The data are processed as many 97 companies. The thechnique of data testing using multiple linear regression analysis.The results showed that the liquidity hasnegative effect and significant to the capital structure, farm size has positive effect ang significant to the capital structure, profitability, growth of assets, and business risk does not have any influence to the capital structure.Keyword : profitability, liquidity, farm size, growth of assets, and business risk